2016
DOI: 10.1186/s12944-016-0382-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of marine n-3 polyunsaturated fatty acids on cardiac autonomic and hemodynamic function in patients with psoriatic arthritis: a randomised, double-blind, placebo-controlled trial

Abstract: BackgroundThe aim of this study was to investigate the effect of marine n-3 polyunsaturated fatty acids (PUFA) on cardiac autonomic function and vascular function in patients with psoriatic arthritis.MethodsThe study was conducted as a randomized, double-blind, placebo-controlled trial, where 145 patients with psoriatic arthritis were supplemented with 3 g of n-3 PUFA or olive oil (control) daily for 24 weeks. Blood pressure, heart rate, heart rate variability (HRV), central blood pressure, pulse wave velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
0
11
0
1
Order By: Relevance
“…The main findings in this study were: (1) The novel assay was technically robust and specific to the target sequence, (2) the fragment was present in serum and plasma, (3) PROM was upregulated in patients with PsA compared to healthy controls, and (4) PROM did not show a difference in patients treated with PUFA treatment. We investigated the PUFA treatment, as marine n-3 PUFAs have previously reduced inflammation, joint pain, and NSAID use in patients with rheumatoid arthritis (RA), and n-3 PUFA supplementation in patients with PsA led to a reduced use of NSAIDs and paracetamol 33 as well as an improved heart rate and heart rate variability 34 . However, there was no correlation to the disease scores, which we also do not see with PROM.…”
Section: Discussionmentioning
confidence: 99%
“…The main findings in this study were: (1) The novel assay was technically robust and specific to the target sequence, (2) the fragment was present in serum and plasma, (3) PROM was upregulated in patients with PsA compared to healthy controls, and (4) PROM did not show a difference in patients treated with PUFA treatment. We investigated the PUFA treatment, as marine n-3 PUFAs have previously reduced inflammation, joint pain, and NSAID use in patients with rheumatoid arthritis (RA), and n-3 PUFA supplementation in patients with PsA led to a reduced use of NSAIDs and paracetamol 33 as well as an improved heart rate and heart rate variability 34 . However, there was no correlation to the disease scores, which we also do not see with PROM.…”
Section: Discussionmentioning
confidence: 99%
“…The other main omega-3 fatty acid is eicosapentaenoic acid or EPA, and omega-3 levels in humans are estimated by the sum of EPA + DHA with docosapentaenoic acid (DPA) being present at much lower concentrations 4 . Positive effects on health from omega-3 fatty acids have been observed for insulin resistance, adult-onset diabetes mellitus 5 7 , hypertension 8 , 9 arthritis 10 , 11 , atherosclerosis 12 , 13 , depression 14 , 15 , thrombosis 16 , some cancers 17 and cognitive decline 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…All these comorbidities increase the risk of cardiovascular complications, not to mention the risk of dying. It has been shown that the implementation of omega-3 acids in a dose equalling 3 g/day for 24 weeks in patients with PA improves the autonomic and hemodynamic functions of the heart by impacting the value of arterial pressure, the central blood pressure and cardiac function, and reducing the heart rate variability (HRV) and pulse wave velocity (PWV) [39]. This has a direct effect on reducing the risk of cardiovascular complications and the sudden death resulting from these events.…”
Section: General Characteristics Of Omega-3 and Omega-6 Acids And Thmentioning
confidence: 99%